A Ideologia urbana : apontamentos para a reconstituição do campo intelectual da reforma urbana no Brasil - Albuquerque, Jersey Oliveira de (2024)
The problem that led to the construction of the object was the dubious stance of established authors of the field in relation to its achievements, especially during the first PT governments in the federal executive. The aim of this thesis is to point out the constituent elements of the intellectual field of Urban Reform in Brazil, based on its cultural unconscious, which we call Urban Ideology. The methodological strategy favoured a qualitative approach to bibliographic material focused on the inventory of the common sense of the intellectual field of Urban Reform in Brazil, based on a debate between its established authors, Brazilian social formation, economic sociology and the theory of social movements. The time frame of our object follows the Brazilian urbanisation process, which began between the 19th and 20th centuries, passing through the Congress of Architects and the struggle for basic reforms in the 1960s, the conservative modernisation of the 1970s-1980s and ending with the dismantling of the Ministry of Cities in 2005. This work dialogues with studies on Ideology in Marx, Engels and Iasi, on Common Sense in Gramsci, Habitus and the Intellectual Field in Bourdieu. We have used the approaches of Bonduki, Maricato and Villaça from those who have established themselves in the field of urban reform in Brazil. Finally, the works of Lefebvre and Marx are used as a guide to understanding the concept of the Urban. As a result of the research, we discovered that Urban Ideology is intrinsically linked to Brazilian social formation and the struggle of the country's working class. However, this ideology has become yet another factor in the field's paralysis in getting out of the paradox of its advanced legislation on Brazilian urban problems and its very limited implementation.